A new spectrophotometric method for the determination of gabapentin usingchromotropic acid (2018)
The purpose was to develop a colorimetric method for determining gabapentin. The method was based on the diazo coupling reaction between diazotized gabapentin and chromotropic acid. The method was validated using ICH guidelines before its application to generic brands of gabapentin. Coupling reaction generated an orange azo adduct whose absorbance was linearly correlated with concentration in the range of 1-6 μg/mL at 470 nm. The method was accurate and precise with recovery range of 97.6-103.1%; intra- and inter-day precisions (%RSD) were less than 0.65% and showed no statistical difference when compared with reference method in the analysis of the dosage forms. The 3D optimization of the adduct revealed an E-type configuration around the azo linkage which would contribute to its stability. The new method can serve as a reliable alternative to the official method for the routine analysis of gabapentin in bulk and dosage forms.